2022
DOI: 10.3389/fped.2022.790273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Immune Dysregulation in COVID-19 Are Different From SARS and MERS: A Perspective in Context of Kawasaki Disease and MIS-C

Abstract: Coronaviruses have led to three major outbreaks to date-Severe Acute Respiratory Syndrome (SARS; 2002), Middle East Respiratory Syndrome (MERS; 2012) and the ongoing pandemic, Coronavirus Disease (COVID-19; 2019). Coronavirus infections are usually mild in children. However, a few children with MERS had presented with a severe phenotype in the acute phase resulting in progressive pneumonic changes with increasing oxygen dependency and acute respiratory distress requiring ventilatory support. A subset of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 159 publications
(160 reference statements)
0
9
0
Order By: Relevance
“…They pointed out that SARS-CoV-2 is characterized by a modified spike polypeptide (S1) with a higher binding affinity to host NRP1 receptors, being responsible for high infectivity and tissue tropism in SARS-CoV-2 infections. The molecular mechanisms of COVID-19 appear to have delayed IFN responses, which are responsible for the high secretion of IL-6, IL-7 and TNF-α, hyperinflammation and worsening of clinical status, with the release of the following autoantibodies to dual specificity mitogen-activated protein kinase kinase 2 (MAP2K2), and to the casein kinase family (Casein kinase 1, alpha 1 (CSNK1A1), Casein kinase 2, alpha 1 (CSNK2A1) and Casein kinase 1, epsilon 1 (CSNK1E1)), found exclusively in MIS-C [ 120 ].…”
Section: Molecular Mechanisms Of Sars-cov-2 Infection and How CD Led ...mentioning
confidence: 99%
“…They pointed out that SARS-CoV-2 is characterized by a modified spike polypeptide (S1) with a higher binding affinity to host NRP1 receptors, being responsible for high infectivity and tissue tropism in SARS-CoV-2 infections. The molecular mechanisms of COVID-19 appear to have delayed IFN responses, which are responsible for the high secretion of IL-6, IL-7 and TNF-α, hyperinflammation and worsening of clinical status, with the release of the following autoantibodies to dual specificity mitogen-activated protein kinase kinase 2 (MAP2K2), and to the casein kinase family (Casein kinase 1, alpha 1 (CSNK1A1), Casein kinase 2, alpha 1 (CSNK2A1) and Casein kinase 1, epsilon 1 (CSNK1E1)), found exclusively in MIS-C [ 120 ].…”
Section: Molecular Mechanisms Of Sars-cov-2 Infection and How CD Led ...mentioning
confidence: 99%
“…Immune dysregulation triggered by COVID-19 infection, hyperinflammation as a result of cytokine storm, endothelial dysfunction, and microangiopathy is responsible for systemic multiorgan involvement. [30][31][32] Elevation of at least two inflammation markers is required for the diagnosis. 11 Among the inflammatory markers, CRP, procalcitonin, ESR, ferritin, IL-6, and D-dimer levels showed remarkable increases.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac involvement was found in 67 to 80% of the children with MIS-C, including ventricular dysfunction, arrhythmias, conduction abnormalities, and coronary artery aneurysms (33–50%, 28–67%, and 13–26%, respectively). 32 Recently, Dhaliwal et al 30 reported that 42.3% of patients with MIS-C had low ejection fraction, 20.8% had coronary aneurysm, 23% had pericardial effusion, and 23% had mitral regurgitation. Abrams et al 35 evaluated 1,080 patients with MIS-C and found that 303 had cardiac involvements such as shock, decreased cardiac function, myocarditis, and coronary artery abnormality (36, 28, 18, and 17%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The median resolution day of the fever was 3 (1-10) days after anakinra treatment. The lymphocyte counts, BNP, CRP, and D-dimer values of the patients became normal on the median day of 5 (1-18), 8.5 (5-53), 10 (1-33), and 11.5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively. The pattern of improvement in EF…”
Section: Outcome and Safetymentioning
confidence: 93%
“…The underlying pathogenesis has not yet been fully elucidated and an abnormal immune response is blamed as the main factor in the pathogenesis of MIS-C. Various cytokines are thought to cause hyperinflammation, including, interleukin-1 (IL-1), interferon-gama (IFNγ), IL-18, IL-6, IL-8, and IL-10 ( 3 , 4 ). While intravenous immunoglobulin (IVIG) and corticosteroids are used in the first line of treatment, anakinra is recommended as a therapeutic option in resistant cases ( 5 ).…”
Section: Introductionmentioning
confidence: 99%